Motivating Elements for FMCG Companies' Organizational Growth - affandi, muhammad; wijayanti, ra afera ratna (LIAISON JOURNAL OF BEST, 2024)
Unilever has been perceived to be an extraordinary FMCG (Fast Moving Consumer Good) company, in top of mind of every customer’s head when it comes to cleaning products, foods and many hygiene products. This has put Unilever on top of the FMCG market. It is proven by the respondents answer that Unilever is also some of the respondent favorite brand when they go their regular convenient store. Even though the quality of Unilever’s product is un-doubly high quality, Unilever doesn’t put a very high price tag for their products, hence another reason why Unilever is the respondents’ top choice when they go to their local convenient store or supermarket. Because of their very good business practice and superior goods, Unilever has become a very prolific firm in the eyes of investors. Investors often see Unilever as a very stable firm to invest. Unilever has proved to be a stable and lucrative investment, for the past decade many has struck goldmine by investing to Unilever. Keywords: FMCG; Unilever; Customer Perspective, Financials, Learning and Growth, Ratio, EPS, Profit, and the ROE.